PEMBERIAN GANTI KERUGIAN HAK ATAS TANAH RAKYAT YANG BERKEADILAN (STUDI KASUS PEMBANGUNAN BENDUNGAN TEMEF DI KABUPATEN TIMOR TENGAH SELATAN) - Barawasi, Azis; Pekuwali, Umbu Lily; Tuba Helan, Yohanes G (Petitum Law Journal, 2023)
Legal research is a systematic and methodological effort to uncover the truth by analyzing and constructing collected data. The focus of this research is on land acquisition for public purposes, with a foundation in legal concepts as the research method. Soerjono Soekanto and Abdulkadir Muhammad view legal research as a scientific activity that uses specific methods, systematic approaches, and thinking to analyze legal phenomena with the goal of problem-solving. Peter Mahmud Marzuki states that legal research is a scientific process to discover legal rules, principles, and doctrines.The aim of this research process is to find correct legal rules by discovering new values beneficial to society. The research type used is normative juridical, referring to legal norms in relevant regulations concerning land acquisition for public purposes. In order to gather information, this research utilizes four approaches: statutory approach, case approach, comparative approach, and conceptual approach. Through these approaches, the researcher seeks to gain a profound understanding of the construction of land acquisition for public purposes. The expected outcome of the research is to contribute to the understanding of agrarian law, especially regarding Land Acquisition Law, by detailing aspects regulated in Law No. 5 of 1960 and Law No. 2 of 2012. Thus, this research provides a conceptual foundation and in-depth understanding of the legal construction in the context of land acquisition for public purposes